Increases in Anxiety and Depression During COVID-19: A Large Longitudinal Study From China - Wu, Shizhen; Zhang, Keshun; Parks-Stamm, Elizabeth J.; Hu, Zhonghui; Ji, Yaqi; Cui, Xinxin (Frontiers in Psychology, 2021)
Although accumulating evidence suggests the COVID-19 pandemic is associated with costs in mental health, the development of students’ mental health, including the change from their previous levels of depression and anxiety and the factors associated with this change, has not been well studied. The present study investigates changes in students’ anxiety and depression from before the pandemic to during the lockdown and identifies factors that are associated with these changes. 14,769 university students participated in a longitudinal study with two time points with a six-month interval. Students completed the Anxiety and Depression subscales of the Symptom Checklist 90 (SCL-90) before the COVID-19 outbreak (October 2020, Time 1), and the Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS) during the pandemic (April 2020, Time 2). The prevalence of anxiety and depression symptoms were 1.44% and 1.46% at Time 1, and 4.06% and 22.09% at Time 2, respectively, showing a 181.94% increase in anxiety and a 1413.01% increase in depression. Furthermore, the increases in anxiety and depression from pre-pandemic levels were associated with students’ gender and the severity of the pandemic in the province where they resided. This study contributes to the gap in knowledge regarding changes in students’ mental health in response to the pandemic and the role of local factors in these changes. Implications for gender differences and the Typhoon Eye effect are discussed.